2012
DOI: 10.1016/j.tips.2011.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Small GTPase regulation of GPCR anterograde trafficking

Abstract: The physiological functions of heterotrimeric G protein-coupled receptors (GPCRs) are dictated by their intracellular trafficking and precise targeting to the functional destinations. Over the past decades, most studies on the trafficking of GPCRs have focused on the events involved in endocytosis and recycling. In contrast, the molecular mechanisms underlying anterograde transport of newly synthesized GPCRs from the endoplasmic reticulum (ER) to the cell surface have just begun to be revealed. In this review,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 58 publications
2
42
0
Order By: Relevance
“…In agreement with this possibility, the same di-acidic motif has been demonstrated to interact with Sec24 and AP3 to control vesicular stomatitis virus protein G (VSVG) transport from the ER and the Golgi body, respectively (44,45). Nevertheless, this study, together with many other reports, indicates that GPCRs may directly interact with the transport machineries to control their export trafficking (23,24,46).…”
Section: Discussionsupporting
confidence: 79%
“…In agreement with this possibility, the same di-acidic motif has been demonstrated to interact with Sec24 and AP3 to control vesicular stomatitis virus protein G (VSVG) transport from the ER and the Golgi body, respectively (44,45). Nevertheless, this study, together with many other reports, indicates that GPCRs may directly interact with the transport machineries to control their export trafficking (23,24,46).…”
Section: Discussionsupporting
confidence: 79%
“…In addition, G protein-coupled olfactory and chemokine receptors are released from the ER but accumulated in the Golgi (14,15), and the opsin mutant E150K is accumulated in the cis and medial Golgi (16). Recent studies have also revealed that Ras-like small GTPases may play important roles in the Golgi to cell surface transport of GPCRs (17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…2 During the last decade, many studies described the involvement of Rab GTPases in the regulation of GPCR trafficking and signaling. Rab GTPases were shown to be key regulators of GPCR anterograde and retrograde transport (Rab1, Rab2, Rab6, and Rab8), [3][4][5][6] endocytosis (Rab5), [7][8][9][10][11] recycling (Rab4 and Rab11), [11][12][13][14][15][16][17][18][19] and degradation (Rab7). 20 We and others established that a direct interaction between a GPCR and a Rab GTPase appears to be necessary in the proper trafficking of the receptor.…”
Section: Gpcrs and The Regulation Of Rab Gtpasesmentioning
confidence: 99%